The influence of family communication, television viewing and peer communication on the orientation of materialism among young adult consumers / Eric Vincent Bindah - Eric, Vincent Bindah (2014)

(untitled)
Materialism among today’s youth has received strong interest among educators, parents, consumer activist and government regulators. Although materialism has long been of interest to consumer researchers, it is not clear whether specific socialization agents in general, and communication environment in particular, can instil materialism in people. The overall objectives of this study are to analyze the effect of family communication, television viewing, and peer communication on young adults’ orientation towards materialism. The theoretical foundation of this study lies on several established theories, which include consumer socialization theory, social comparison theory, social learning theory, cultivation theory, self-determination theory, Maslow’s human need theory, symbolic self-completion theory and the life course theory. Studies have found two relatively uncorrelated dimensions of communication structure which are associated with family communication: socio and concept-oriented family communication. The development of religiously-oriented family communication structure was primarily based on prior studies on religiousness. Studies have also found that exposure to a television viewing and peer communication could significantly affect the beliefs and behaviours of large numbers of people. The research framework of this study hypothesized that young adult person’s exposure to a socio-oriented family communication structure at home during adolescent years was positively associated with their orientation towards materialism in their adulthood. It was also hypothesized that young adult person’s exposure to a concept-oriented, and religiously-oriented family communication structures at home during adolescent years were negatively associated with their orientation towards materialism in their adulthood. Next, it was hypothesized that young adults’ exposure to television viewing at home during adolescent years would have a positive effect on their orientation towards materialism in adulthood. Based on previous studies, it was hypothesized that young adult persons’ exposure to a socio-oriented, concept-oriented and religiously-oriented family communication structures, and television viewing at home during adolescent years would have a positive effect on peer communication. It was also hypothesized that young adult person’s communication with their peers during adolescent years was positively associated with their orientation towards materialism in their adulthood. Finally, it was hypothesized that peer communication would mediate the relationship between young adults’ exposure to a socio-oriented, concept-oriented, and religiously-oriented family communication structure and television viewing at home during adolescent years and their orientation towards materialism in their adulthood. A survey was used to explore the complex relationship between young adults’ family-oriented communications, television viewing, peer communication and materialism. The survey questionnaire consisted of 51 questions. This study employed non-probability sampling technique and was based on convenience sampling method. Respondents consisted of young adults mostly college students in higher learning institutions in Malaysia, and the data were collected for a period of four months. The survey questionnaires were given to 1,200 randomly selected university and college students and 1002 completed questionnaires were returned in the survey, for a iv response rate of 83.5%. The reliability analysis of all measurement scales ranged from 0.54 to 0.84. The exploratory measurements assessment included exploratory factor analysis, and internal consistency reliability for all the constructs studied. Demographic differences were examined among all the constructs of the study. Preliminary statistical procedures were employed to examine possible significant group differences in all the constructs based on gender, age, ethnicity, religion, marital status, education, and income. Structural Equation Modelling (SEM) technique was used to examine the overall hypothesised model and specific hypotheses testing. The hypotheses testing were conducted based on a partially mediated model. Out of ten (10) hypotheses tested in the hypothetical model for this study, eight (8) hypotheses were supported. Young adult person’s exposure to a socio-oriented family communication structure at home during adolescent years was significantly and positively associated with their orientation towards materialism in their adulthood. Young adult person’s exposure to a socio-oriented, concept-oriented, and religiously-oriented family communication structure at home during adolescent years had a significant positive effect on peer communication. The results also indicated that young adult person’s communication with their peers during adolescent years was significantly and positively associated with their orientation towards materialism in their adulthood. Peer communication partially mediated the relationship between socio-oriented family communication and materialism. Peer communication fully mediated the relationship between concept-oriented family communication and materialism, and between religiously-oriented family communication and materialism. This study is significant in many ways. First, it provided an insight into how the family environment during adolescent years influenced the orientation of materialism among young adults. This study found that young adults who were exposed to a socio-oriented family communication during adolescent years were inclined towards materialism regardless of whether or not they communicated with their peers. Although there was no significant direct association between young adults’ who were exposed to a concept-oriented, and religiously-oriented family communication during adolescent years and their orientation towards materialism, the results indicated that those who frequently communicated with their peers during adolescent years were oriented towards materialism in adulthood. Regardless of the type of family communication structure at home, it appeared that peer communication during adolescent years exerted a great influence in young adults’ orientation towards materialism. This study has its own limitations. For instance, parental influence is not limited to family communication environment alone. Other important variables such as family structure need considerable attention. Future research could provide a model which would explore the aspects of parenting styles, peer influence, and television programmes in detail. Last but not least, this study was an attempt to provide information which could be useful to help marketers to get a better understanding of their target consumers. On the other hand, government agencies could for instance, implement policies and programmes through their various affiliations to educate parents on how to foster relationship with their children to discourage excessive consumption habits among young consumers.